Effect of working fluids and internal diameters on thermal performance of vertical and horizontal closed-loop pulsating heat pipes with multiple heat sources - Kammuang-Lue N. (2017)
Some electrical applications have a number of heat sources. The closed-loop pulsating heat pipe (CLPHP) is applied to transfer heat from these devices. Since the CLPHP primarily transfers heat by means of the working fluid's phase change in a capillary tube, the thermal performance of the CLPHP significantly depends on the working fluid type and the tube's internal diameter. In order to provide the fundamental information for manufacturers of heat exchangers, this study on the effect of working fluids and internal diameters has been conducted. Three electrical plate heaters were installed on the CLPHP as the heat sources. The experiments were conducted by varying the working fluid to be R123, ethanol, and water, at the internal diameter of 1.0 mm, 1.5 mm, and 2.0 mm. For each set of the same working fluid and internal diameter, the input heat fluxes of the heat sources were also made to vary within six different patterns. It can be concluded that when the latent heat of evaporation increases - in the case of vertical CLPHP - and when the dynamic viscosity of the liquid increases - in the case of horizontal CLPHP - the thermal performance decreases. Moreover, when the internal diameter increases, the thermal performance increases for both of vertical and horizontal CLPHP.